Applications of ultra-lightweight cement composite in flat slabs and double skin composite structures. (15th May 2016) - Yan, Jia-Bao; Wang, Jun-Yan; Liew, J.Y.Richard; Qian, Xudong
Highlights: Develop ultra lightweight cement composite (ULCC) for offshore and onshore structures. Develop double skin composite (DSC) elements for Arctic offshore structures with ULCC. Report tests on flat slabs with ULCC under localized ice loads. Report tests on DSC plates and shells under localized ice loads. Develop design equations on strengths of flat slabs and DSC plates and shells. Abstract: Ultra-lightweight cement composite (ULCC) has been developed for building and offshore constructions. This paper aims to apply the ULCC in the flat slabs of commercial buildings and double-skin-composite (DSC) ice-resistant walls in the Arctic offshore structures. After developing the structural concepts, quasi-static tests were performed on ULCC flat slabs, DSC slabs, and DSC shells to investigate their ultimate strength behaviors under concentrated loads. General behaviors of these specimens were reported, and the influences of flexural reinforcing ratio (or steel content), volume fraction of the fibers in ULCC, and depth of cross section on ultimate strength behaviors were studied and analyzed. A design approach with a series of equations was developed to predict the ultimate resistances of the reinforced flat slabs, DSC slabs and shells with ULCC. This design approach incorporated influences of fiber content, the resistance contributed by top steel skin, the influence of the curvature on the size of the punching cone in DSC shells, and the modifications on the punching shear resistance by the stud connectors in DSC structure. The accuracy of the design approach is checked against the reported 15 tests. Design recommendations were given for the flat slabs and DSC structures with ULCC.